Ligational aspects of some 4f metal complexes of a mesogenic Schiffbase, N,N’- di-(4-dodecyloxysalicylidene)-1’,3’-diaminopropane: Synthesis and spectral studies - Shrestha, Prem; Shakya, Pawan (Journal of Nepal Chemical Society, 2022)
A liquid crystalline (smectic-F and smectic-A phases)Schiff base, N,N′-di-(4-dodecyloxysalicylidene)-1′,3′-diaminopropane(abbreviated as H2L) and a series of lanthanide (III) complexes of the type [Ln2(LH2)3(NO3)4](NO3)2, (Ln = La, Pr, Nd, Sm, Eu, Gd, Tb, Dy and Ho) have been synthesized and characterized by elemental analysis, mass spectrometry, FTIR, and UV-Vis spectral techniques. The IR spectral data imply bidentate chelation of the Schiff base in its zwitterionic form (as LH2) to the LnIII ions through two phenolate oxygens, rendering the overall geometry of the complexes possibly to distorted mono-capped octahedra. The optical and thermal behavior studies (POM & DSC techniques) reveal that despite H2L being mesogenic, none of the LnIII complexes synthesized under this study exhibits mesomorphism. Fluorescence studies show emissions of H2L and SmIII complexx.